Comparisons of orthodontic residents' performance and attitudes using 2D, 3D, and virtual reality surgical simulation methods. Issue 8 (31st March 2021) - Sytek, Lauren; Inglehart, Marita R.; Ramaswamy, Vidya; Aronovich, Sharon; Edwards, Sean; Kim‐Berman, Hera
Abstract: Purpose: Advances in virtual reality technology for surgical simulation methods may improve diagnosis and treatment planning of complex orthognathic surgery cases. The objectives were to assess orthodontic residents' performance and attitudes when treatment planning orthognathic surgery cases using two‐dimensional (2D) digital, three‐dimensional (3D) digital, and virtual reality (VR) surgical simulations. Methods: The study had a mixed methods study design involving 20 graduate orthodontic residents. Their previous experiences, confidence, and competence with orthodontic diagnosis and surgical treatment planning were assessed with a baseline survey. Each resident completed 2D, 3D, and VR treatment planning and simulation tasks in a randomized order and recorded their diagnosis, objectives, treatment plan, and special surgical concerns for each case using a treatment planning worksheet. The worksheets were scored and quantitative data were analyzed. Attitudinal responses to the simulation experience were captured with a post‐survey and interview. Results: The number of total prescribed surgical movements was greater for 3D and VR simulation methods ( p = 0.001). There were no differences in the overall total written treatment plan analysis score among the three surgical simulation tasks. Participants took longer to complete the VR and 3D tasks ( p < 0.001) and asked more questions regarding manipulation ( p < 0.001) and software features ( p < 0.002) for higher fidelity tools. Analysis of qualitative feedback showed positive attitudes toward higher fidelity tools with regard to visualization, manipulation, and enjoyment of the task. Conclusions: The results demonstrate that simulation methods of increased fidelity (3D and VR) are appropriate alternatives to 2D conventional orthognathic surgical simulation methods when combined with traditional records. Qualitative feedback confirms residents' readiness to adopt VR simulation. However, comprehensive training is needed to increase familiarity and comfort with using the new technology.